THE EFFECTIVENESS OF BIOFERTILIZER ON PLANT GROWTH SOYB EA N â€œEDAM AM Eâ€ (Glycin max) - Diah Sudiarti (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2017)
This study aimed at determining the effectiveness of biofertilizer with different concentrations on plant growth of soybean â€œedamameâ€ (glycin max). Biofertilizer in this study consists of microbial consortia (lactobacillus, pseudomonas, bacillus, saccharomyces, rhizobium, azotobacter, azospirillum, and cellulomonas). The treatment consists of 3 biofertilizer concentrations (25%, 50%, dan 75%), as well as the negative control and positive control (100% chemical fertilizer equivalent 5g/plant). The result showed that treatment b3 (biofertilizer 75%) gave better results on plant growth compared with other treatments.